2014
DOI: 10.1523/jneurosci.3782-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Brief Cortical Deactivation Early in Life Has Long-Lasting Effects on Multisensory Behavior

Abstract: Detecting and locating environmental events are markedly enhanced by the midbrain's ability to integrate visual and auditory cues. Its capacity for multisensory integration develops in cats 1-4 months after birth but only after acquiring extensive visual-auditory experience. However, briefly deactivating specific regions of association cortex during this period induced long-term disruption of this maturational process, such that even 1 year later animals were unable to integrate visual and auditory cues to enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Why then did this capability for multisensory integration not develop rapidly in animals whose cortices were deactivated briefly during early development, as reported by Rowland et al 146 ? Superior colliculus neurons in these animals were unable to integrate cross-modal cues even after more than a year of experience in a normal environment.…”
Section: Ongoing Plasticitymentioning
confidence: 86%
See 1 more Smart Citation
“…Why then did this capability for multisensory integration not develop rapidly in animals whose cortices were deactivated briefly during early development, as reported by Rowland et al 146 ? Superior colliculus neurons in these animals were unable to integrate cross-modal cues even after more than a year of experience in a normal environment.…”
Section: Ongoing Plasticitymentioning
confidence: 86%
“…Implanting a polymer infused with an inhibitory agent (that is, muscimol) over the association cortex silenced its neurons during the period (postnatal weeks 4–12) in which cross-modal sensory experience is being encoded and superior colliculus multisensory integration capability is first being expressed 146 . Even a year or more after the cortical inputs had been reactivated, these animals were unable to use visual and auditory cues synergistically to enhance their performance in a standard superior colliculus-mediated detection and localization task (FIG.…”
Section: Experience and Cortical Inputsmentioning
confidence: 99%
“…Of these, ipsilateral inputs from the anterior ectosylvian sulcus and the rostral lateral suprasylvian sulcus are particularly important for multisensory processing in SC. Should these associational cortices be deactivated or ablated at any stage of life, SC neurons are rendered incapable of integrating cross-modal cues (Wallace & Stein, 2000;Jiang et al 2001;Alvarado et al 2007;Rowland et al 2014;Xu et al 2017). Thus, it is plausible that RF shifting may occur first in these cortices, with the result being transferred to SC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, based on electrophysiological evidence, it was argued that multisensory systems mold to one another to take into account the statistical regularities of the physical environment within which we live. More specifically, researchers observed that in the temporal domain, for instance, multisensory gain was the greatest when presentation of auditory and visual cues was offset in order to compensate for the differential times of transmission in medium (light being faster than sound) and neural transduction (the auditory system being faster than the visual one) of these modalities . More causally, animals were reared whose sole sensory experience was that of synchronized audiovisual stimuli that were nonetheless spatially disparate by 18–30° of visual angle.…”
Section: Multisensory Integrationmentioning
confidence: 99%